Application of Soil Conservation in Oil Palm Plantation - Halus Satriawan; Zahrul Fuady; Zara Yunidar (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2015)
Oil palm development in Bireuen very important to increase the regional incomes, however, is also faced with the danger of land resources and environmental damage because it sited in an area with a slope 15-35%, with land capability class III – VII. This study aimed to obtain soil and water conservation techniques are most appropriate and optimal in each land capability class. The studies were conducting by Experimental Method (Standard Erosion Plot). Testing of soil and water conservation techniques was done with land capability base. On land capability class III was tested four treatments, namely: the system of farmers; individual terrace (horseshoe); individual terraces + strips plant; cover crops + organic fertilizer.Land in class IV was tested  four treatments, namely: the system of farmers; sediment trap; sediment trap + vertical mulching; sediment trap + cover crops + organic fertilizer. Results of measurements of surface runoff and erosion on land capability class III, soil conservation techniques capable of suppressing erosion compared to the control treatment, in this case the best treatment is the cover crops and organic fertilizers. Cover crops and organic fertilizers is able to suppress runoff and erosion by 23.73% and 27.29% compared to controls. As well as the application of soil conservation techniques in land capability class IV with sediment trap + cover crop and organic fertilizer is very effective in controlling runoff and erosion to 45.81 and 45.63% compared to controls.